Profilin Expression Is Regulated by Bone Morphogenetic Protein (BMP) in Osteoblastic Cells. Issue 3 (20th November 2015) - Lin, Wanting; Ezura, Yoichi; Izu, Yayoi; Aryal A.C, Smriti; Kawasaki, Makiri; Na Mahasarakham Chantida, Pawaputanon; Moriyama, Keiji; Noda, Masaki
ABSTRACT: Profilin 1 (Pfn1) regulates cytoskeletal reorganization and migration, but its role in osteoblasts is not known. BMP (bone morphogenetic protein) is a multifunctional cytokine involved in osteoblastic differentiation and promotes bone regeneration and repair. Although several molecules are known to modulate BMP signaling, mechanisms that determine the levels of BMP action in osteoblastic function are still incompletely understood. We therefore examine the expression of Pfn1 in osteoblasts and its role in BMP‐induced differentiation in osteoblasts. In osteoblastic MC3T3‐E1(MC) cells, Pfn1 mRNA is expressed constitutively and its expression levels are declined during the culture in a time dependent manner in contrast to the increase in alkaline phosphatase activity revealing that Pfn1 expression is down regulated along with differentiation. To test the effects of osteoblastic differentiation on Pfn1expression further, MC cells are treated with BMP. BMP treatment suppresses the levels of Pfn1 mRNA. This suppressive effect of BMP is time dependent and further down regulation of Pfn1 mRNA levels is observed when the BMP treatment is continued for a longer period of time. Pfn1mRNA knock down (KD) by siRNAs enhances BMP‐induced increase in alkaline phosphatase (Alp) activity in MC cells. To analyze the regulatory mechanism, Alp mRNA levels are examined and Pfn1 KD enhances the BMP‐induced increase in the levels of Alp mRNA expression. Furthermore, Pfn1 KD enhances BMP‐induced transcriptional expression of luciferase reporter activity via BMP response element in osteoblasts. These data indicate that Pfn1 is a novel target of BMP and suppresses BMP‐induced differentiation of osteoblasts at least in part via transcriptional event. J. Cell. Biochem. 117: 621–628, 2016. © 2015 Wiley Periodicals, Inc.